Barium and Radium Complexation with Ethylenediaminetetraacetic Acid in Aqueous Alkaline Sodium Chloride Media - Matyskin, Artem V. (J Solution Chem, 2017)
The speciation of Ra(2+) and Ba(2+) with EDTA was investigated at 25 °C in aqueous alkaline NaCl media as a function of ionic strength (0.2–2.5 mol·L(−1)) in two pH regions where the EDTA(4−) and HEDTA(3−) species dominate. The stability constants for the formation of the [BaEDTA](2−) and [RaEDTA](2−) complexes were determined using an ion exchange method. Barium-133 and radium-226 were used as radiotracers and their concentrations in the aqueous phase were measured using liquid scintillation counting and gamma spectrometry, respectively. The specific ion interaction theory (SIT) was used to account for [NaEDTA](3−) and [NaHEDTA](2−) complex formation, and used to extrapolate the logarithms of the apparent stability constants (log(10) K) to zero ionic strength (BaEDTA(2−): 9.86 ± 0.09; RaEDTA(2−): 9.13 ± 0.07) and obtain the Ba(2+) and Ra(2+) ion interaction parameters: [ε(Na(+), BaEDTA(2−)) = − (0.03 ± 0.11); ε(Na(+), RaEDTA(2−)) = − (0.10 ± 0.11)]. It was found that in the pH region where HEDTA(3−) dominates, the reaction of Ba(2+) or Ra(2+) with the HEDTA(3−) ligand also results in the formation of the BaEDTA(2−) and RaEDTA(2−) complexes (as it does in the region where the EDTA(4−) ligand dominates) with the release of a proton. Comparison of the ion interaction parameters of Ba(2+) and Ra(2+) strongly indicates that both metal ions and their EDTA complexes have similar activity coefficients and undergo similar short-range interactions in aqueous NaCl media.